The Politics Today Companion to West European Politics - Roberts, Geoffrey K. (Manchester University Press, 2003)
This book is an essential reference guide for students of West European politics and West European area studies. A perfect companion to European politics today (by the same authors), it contains details of major events, political leaders, important dates, organisations and recent elections, all in an accessible, easy-to-read format. A comprehensive reference work, the book also provides a sound historical background for students of contemporary Europe. It covers the information and terms of reference students need to know to understand developments in European politics from the Second World War to the present day. Much of the book is devoted to those European countries most often featured in comparative courses in colleges and universities: the United Kingdom, France, Germany, Italy and Spain as well as the European Union. Also included are details of personalities and events which have proved decisive for smaller and less familiar European democracies. From Resistance leaders to presidents, civil wars to scandals, the forces shaping the Europe of today are detailed in this book. This book is ideal for undergraduate students on politics, European studies and area studies courses.